Design and Implementation of Sucirata-Based Instrusion Detection System as a Network Security System Cloud Computers - Idrus, Ali; Sugiyanta, Lipur; Nugraheni, Murien; Subhiyanto, S (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Cloud computing is currently being developed and widely used by companies that require large and efficient computing resources. As technology evolves, security threats in cloud services continue to increase. Various threats in cloud computing technology can be avoided by maximizing the identification of security holes. Information threats associated with cloud computing require network and service security against possible attacks. Suricata is a threat detection identifier supported by existing rules. When an attack is detected, Suricata will create a log of the attack committed, Suricata can also perform automatic detection at level 7. The author collected the results of the attack in a log. Sign Suricata and the authors also evaluate whether Suricata can detect port scanning, brute force, denial of service, and backdoors for Cloud Computing. From the test results, optimal results were obtained from the results of attacks detected by the Suricata Intrusion Detection System (IDS) logs in the /var/log/suricata/fast directory.log, the author added that the Suricata configuration is not only for detection, so it can also run drops if there is suspicious activity using network filters that already exist in Suricata and manipulated configuration assumptions to optimally improve security in the cloud.